Evaluación de estrategias para que Sanima provea acceso asequible de agua potable en comunidades desatendidas de Lima garantizando su sostenibilidad financiera y crecimiento a largo plazo - Tokjuman, Aisha (2025)
In Lima, Peru, access to safe drinking water and sanitation remains a critical challenge. Families in peri-urban districts such as Pamplona often rely on costly and unsafe alternatives, exposing them to severe health risks and financial burdens. The result is recurring illness, additional household expenses, and ongoing insecurity in daily life. Sanima, a social enterprise based in Lima, addresses this issue through a container-based sanitation (CBS) model that provides safe and dignified toilet solutions. However, to ensure long-term financial stability and expand its social impact, Sanima must diversify its revenue streams. The purpose of this thesis was therefore to identify complementary business model ideas and evaluate their suitability for Sanima’s context. The study applied a qualitative methodology, with multiple iterative cycles in which different concepts were tested and refined through user feedback and contextual analysis. Among these, the model of water vending machines, supplied by Sanima’s potential partner Aguavida, emerged as particularly promising. These units provide affordable, clean water while reducing plastic waste. Located in high-traffic supermarkets, they guarantee accessibility for urban families and simultaneously generate brand visibility for Sanima. The solution addresses multiple dimensions at once: it improves health and quality of life for households, reduces household budgets, mitigates environmental pressures, and creates a reliable revenue stream for Sanima. With a clear value proposition for users, a scalable structure, and strategic partnerships with actors such as Intercorp and Aguavida, the initiative demonstrates strong potential to secure short-term income and, over the long term, significantly improve access to water and sanitation in Lima.